2020
DOI: 10.1016/j.toxlet.2020.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the absorbed dose after exposure to surgical smoke in an operating room

Abstract: We would like to thank the technical staff of the laboratory of the KU Leuven for all analysis and the students in the master of Epidemiology (UAntwerpen), Solomon Wfula, Hassard Sempeera and Innocent Mugume for the statistical support. We express our gratitude to the entire medical staff that participated in the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 18 publications
0
15
0
1
Order By: Relevance
“…In this study, we observed that pollutant exposure levels of the assistant surgeon were much higher than those of other medical staff, despite the proximity of the assistant surgeon to the main surgeon. Previous studies of smoke from laparoscopic surgery have also pointed to high levels of assistant surgeon exposure to smoke from patients' wounds [ 58 ]. Field measurements by et al at St. Olav Hospital also found that assistant surgeons were significantly more sensitive to particulate matter of various sizes during certain surgeries than other medical staff [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed that pollutant exposure levels of the assistant surgeon were much higher than those of other medical staff, despite the proximity of the assistant surgeon to the main surgeon. Previous studies of smoke from laparoscopic surgery have also pointed to high levels of assistant surgeon exposure to smoke from patients' wounds [ 58 ]. Field measurements by et al at St. Olav Hospital also found that assistant surgeons were significantly more sensitive to particulate matter of various sizes during certain surgeries than other medical staff [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…3,4,11,12 There was also evidence of histopathological changes in the nasal mucosa of healthcare professionals, 5 and changes in the blood count of neutrophils and lymphocytes. 17 The presence of benzene and toluene in the urine was observed 1,18 regarding organic absorption of toxic substances identified in surgical smoke by patients and healthcare professionals, or even increased exposure levels to formaldehyde and acetaldehyde. 6 The main signs and symptoms identified and their frequency of appearance in the studies which compose the present review are shown in Table 5.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…Surgical smoke can be seen and its odor is smelled, being composed of 95% water vapor and 5% by products of combustion and cellular waste. 1 This waste includes chemical compounds such as benzene and toluene, and biological materials such as blood particles, viruses, bacteria, mutagenic and cytotoxic agents in aerosols. 2 The amounts and composition of by products can vary according to the type of surgery, target tissue and technique used by the surgeon, and exposure to these compounds can cause cumulative damage to the health of patients and healthcare professionals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency of these ventilation principles in terms of contamination control and reduction of Surgical Site Infections (SSIs) has been questioned in several works paying attention only to the health risks for the patient [4,5,[50][51][52][53]. Few works have studied the influence of the ventilation system on the health risks for the medical team due to surgical smoke [16,17,24,54].…”
Section: Introductionmentioning
confidence: 99%